2002
DOI: 10.1074/jbc.m200762200
|View full text |Cite
|
Sign up to set email alerts
|

Prp43 Is an Essential RNA-dependent ATPase Required for Release of Lariat-Intron from the Spliceosome

Abstract: Members of the family of DEXH/D-box proteins are involved in all major RNA transactions, including transcription, translation, ribosome biogenesis, and pre-mRNA splicing (1, 2). DEXH/D-box proteins can hydrolyze NTP to NDP in a reaction that is stimulated by, or dependent on, a nucleic acid cofactor. Although several DEXH/D family members exhibit RNA helicase activity in vitro, the action of DEXH/D-box NTPases may not be limited to the unwinding of RNA duplexes. Recent studies suggest that they can act as "RNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
257
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(278 citation statements)
references
References 39 publications
17
257
0
4
Order By: Relevance
“…Both the localization of endogenous DDX15 to nuclear speckles and the coprecipitation of spliceosomal U RNAs from a HeLa cell extract suggest that DDX15 might play a role in pre-mRNA splicing+ This hypothesis is in agreement with the observations that the yeast ortholog of DDX15, Prp43, is involved in a late step in pre-mRNA splicing, namely spliceosome disassembly (Arenas & Abelson, 1997;Martin et al+, 2002)+ Also the murine ortholog, mDEAH9, contains a similar activity, as it could functionally replace Prp43 in yeast (Gee et al+, 1997)+ DDX15 represents the first example of a human DEAH-box protein that localizes to both nuclear speckles and nucleoli in mammalian cells+ This suggests that besides a function in pre-mRNA splicing, DDX15 also plays a role in other processes+ In yeast, several DEAH-box proteins, including Dhr1p and Dhr2p, localized to nucleoli, where they function in pre-rRNA processing (Colley et al+, 2000)+ In analogy, the nucleolar pool of DDX15 might function in pre-rRNA processing+ What then could be the functional relevance of the DDX15-La interaction? In yeast, the La ortholog, Lhp1p, has been shown to be involved in the biogenesis of the U1, U2, U4, U5, and U6 snRNPs (Pannone et al+, 1998;Kufel et al+, 2000;Xue et al+, 2000)+ La is the first protein to bind to newly transcribed RNA polymerase III transcripts, including U6 snRNA+ A fraction of the La protein molecules is known to reside in the nucleolus (Pruijn et al+, 1997;Maraia & Intine, 2002), and several RNA polymerase III transcripts like U6 snRNA (Lange & Gerbi, 2000), pre-tRNAs (Bertrand et al+, 1998), SRP RNA (Jacobson & Pederson, 1998;Grosshans et al+, 2001), 5S rRNA (Michael & Dreyfuss, 1996), RNAse P (Jarrous et al+, 1999), and RNAse MRP RNA (Jacobson et al+, 1995) are (transiently) localized to this compartment as well+ Therefore it has been suggested that La accompanies these RNAs to the nucleolus )+ We observed a (partial) colocalization of DDX15 and La in the nucleoli+ Moreover, our results suggest that there is only a low level of association between La and DDX15 indicating that only part of the La molecules associate with DDX15+ It is possible that this interaction only occurs in the nucleoli or in another nuclear subcompartment, where the action of both proteins is required in concert+ It is tempting to speculate that La recruits DDX15 to the RNAs mentioned above in the nucleolus, where DDX15 might be required for further processing of these RNAs and for their assembly into RNPs+ Proof for such a concerted action of La and DDX15 might be provided by yeast strains lacking both Lhp1p and the yeast DDX15 protein, Prp43+…”
Section: Functional Aspects Of Ddx15 and The Interaction Between La Asupporting
confidence: 82%
See 2 more Smart Citations
“…Both the localization of endogenous DDX15 to nuclear speckles and the coprecipitation of spliceosomal U RNAs from a HeLa cell extract suggest that DDX15 might play a role in pre-mRNA splicing+ This hypothesis is in agreement with the observations that the yeast ortholog of DDX15, Prp43, is involved in a late step in pre-mRNA splicing, namely spliceosome disassembly (Arenas & Abelson, 1997;Martin et al+, 2002)+ Also the murine ortholog, mDEAH9, contains a similar activity, as it could functionally replace Prp43 in yeast (Gee et al+, 1997)+ DDX15 represents the first example of a human DEAH-box protein that localizes to both nuclear speckles and nucleoli in mammalian cells+ This suggests that besides a function in pre-mRNA splicing, DDX15 also plays a role in other processes+ In yeast, several DEAH-box proteins, including Dhr1p and Dhr2p, localized to nucleoli, where they function in pre-rRNA processing (Colley et al+, 2000)+ In analogy, the nucleolar pool of DDX15 might function in pre-rRNA processing+ What then could be the functional relevance of the DDX15-La interaction? In yeast, the La ortholog, Lhp1p, has been shown to be involved in the biogenesis of the U1, U2, U4, U5, and U6 snRNPs (Pannone et al+, 1998;Kufel et al+, 2000;Xue et al+, 2000)+ La is the first protein to bind to newly transcribed RNA polymerase III transcripts, including U6 snRNA+ A fraction of the La protein molecules is known to reside in the nucleolus (Pruijn et al+, 1997;Maraia & Intine, 2002), and several RNA polymerase III transcripts like U6 snRNA (Lange & Gerbi, 2000), pre-tRNAs (Bertrand et al+, 1998), SRP RNA (Jacobson & Pederson, 1998;Grosshans et al+, 2001), 5S rRNA (Michael & Dreyfuss, 1996), RNAse P (Jarrous et al+, 1999), and RNAse MRP RNA (Jacobson et al+, 1995) are (transiently) localized to this compartment as well+ Therefore it has been suggested that La accompanies these RNAs to the nucleolus )+ We observed a (partial) colocalization of DDX15 and La in the nucleoli+ Moreover, our results suggest that there is only a low level of association between La and DDX15 indicating that only part of the La molecules associate with DDX15+ It is possible that this interaction only occurs in the nucleoli or in another nuclear subcompartment, where the action of both proteins is required in concert+ It is tempting to speculate that La recruits DDX15 to the RNAs mentioned above in the nucleolus, where DDX15 might be required for further processing of these RNAs and for their assembly into RNPs+ Proof for such a concerted action of La and DDX15 might be provided by yeast strains lacking both Lhp1p and the yeast DDX15 protein, Prp43+…”
Section: Functional Aspects Of Ddx15 and The Interaction Between La Asupporting
confidence: 82%
“…The N-terminal and C-terminal extensions of DDX15 seem to play a role in the subcellular localization of DDX15+ Using the anti-hPrp43/DDX15 rabbit serum, we showed that endogenous DDX15 localizes to nuclear speckles and, surprisingly, to nucleoli of HEp-2 cells (Fig+ 7)+ The subcellular localization of DDX15 to nuclear speckles and colocalization with the splicing factor U2B0 and the Sm-proteins are in agreement with the fact that the yeast ortholog Prp43 has been reported to be involved in spliceosome disassembly (Arenas & Abelson, 1997)+ Moreover, recently it was reported by Martin et al+ (2002) that Prp43 represents an essential RNA-dependent ATPase required for the release of the excised lariat-intron from the spliceosome+ The observation that DDX15 also accumulates in nucleoli suggests that, besides functioning in splicing, DDX15 is also involved in other processes (see below)+ Data from the literature on the localization of DDX15 and its homologs is very limited+ The nucleolar accumulation of DDX15 was recently corroborated by the proteomic analysis of purified human nucleoli, in which DDX15 was identified as a nucleolar protein (Andersen et al+, 2002)+ Whereas several DExD-box RNA helicases were identified, no other members of the DExH-box RNA helicase family were identified in this analysis of nucleolar proteins (Andersen et al+, 2002)+ Imamura et al+ (1997) reported that a GFP-tagged version of DBP1 localized to the nucleus of HeLa cells+ However, they did not observe the nuclear speckles and nucleolar accumulation we report in this article+ The mouse ortholog of DDX15, mDEAH9, was shown to localize to nuclear speckles, but was not observed in the nucleoli (Gee et al+, 1997)+ The discrepancies between our results and the results obtained with DBP1 and mDEAH9 might be explained by sequence differences between the three proteins+ First, the sequence of DBP1 contains a frameshift, resulting in an alternative C-terminal end in comparison with DDX15; second, whereas the murine and human proteins are almost identical over the whole protein sequence, mDEAH9 does have a shorter C-terminal part compared to DDX15 (see Fig+ 2)+ Based on these observations we suggest that the C-terminal part is important for the subnuclear localization of DDX15+ This is corroborated by the results from the deletion analysis of DDX15+ In agreement with the nuclear localization of DDX15, we identified a region required for its entry into the nucleus between amino acids 63 and 153 (see Fig+ 10)+ A deletion of amino acids 690 to 795 abolished its association with nuclear speckles, substantiating the importance of this region for its subnuclear localization+ Other DExD/H family members, like hPrp16 and HRH1, also have been reported to accumulate in speckles+ The localization of hPrp16 and HRH1 to nuclear speckles is mediated by their RS domains (Ohno & Shimura, 1996;Ortlepp et al+, 1998), which is not discernable in the DDX15 sequence+ Detailed analysis of the region spanning amino acids 690 to 795 is therefore needed to identify the amino acids involved in the targeting of DDX15 to nuclear speckles+ The nucleolar accumulation of DDX15 appeared to require two, spatially separated regions of the protein (Fig+ 10)+ Deletion of amino acids 1 to 62 in the N-terminal part abolished nucleolar accumulation, whereas the association with nuclear speckles remained unaffected+ The sequence of this region is characterized by the presence of a stretch of alternating basic and acidic residues between amino acids 25 and 60+ This repeat can be subdivided into two parts based FIGURE 10. S...…”
Section: Subcellular Localization Of Ddx15supporting
confidence: 79%
See 1 more Smart Citation
“…The essential role of Prp43 in the disassembly of the ILS has long been established (Martin et al 2002;Tsai et al 2005). However, recent experiments in vitro indicated that the helicase activity of Brr2 also plays a role in this process (Small et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation of the IL RNA from the ILS requires the DEAH-box RNA helicase Prp43 (Arenas and Abelson 1997;Martin et al 2002;Tsai et al 2005). At the same time, the remaining spliceosomal core, containing the U2/U6 and U5 snRNPs, is also disassembled (Tsai et al 2005).…”
mentioning
confidence: 99%